2014
DOI: 10.1063/1.4863308
|View full text |Cite
|
Sign up to set email alerts
|

Bichromatic random laser from a powder of rhodamine-doped sub-micrometer silica particles

Abstract: Articles you may be interested inTiO2@Silica nanoparticles in a random laser: Strong relationship of silica shell thickness on scattering medium properties and random laser performance Appl. Phys. Lett. 104, 081909 (2014); 10.1063/1.4865092SiO 2 nanoparticles as scatterers for random organic laser action in red fluorescent dye 4-(dicyanomethylene)-2tert-butyl-6(1,1,7,7-tetramethyljulolidyl-9-enyl)-4 H -pyran doped polystyrene films Random lasing emission from a red fluorescent dye doped polystyrene film contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Dye-based RLs are highly efficient, and have been used as a platform for demonstration of optical effects such as the bichromatic emission due to monomers and dimers in Rhodamines [15][16][17], multi-photon excitation [18][19], and low spatial coherence [20]. In spite of the promising characteristics of dye-based RLs, the dye photodegradation, enhanced due to the presence of the scatterers is a drawback for the basic investigation and practical application of these systems [21,23].…”
Section: Introductionmentioning
confidence: 99%
“…Dye-based RLs are highly efficient, and have been used as a platform for demonstration of optical effects such as the bichromatic emission due to monomers and dimers in Rhodamines [15][16][17], multi-photon excitation [18][19], and low spatial coherence [20]. In spite of the promising characteristics of dye-based RLs, the dye photodegradation, enhanced due to the presence of the scatterers is a drawback for the basic investigation and practical application of these systems [21,23].…”
Section: Introductionmentioning
confidence: 99%
“…[3] Later on, the bichromatic emission phenomena in the systems consisting rhodamine 640 in methanol and TiO 2 particles were studied by Sha et al [8,9] Recently, the bichromantic RL was also observed from the alumna porous ceramic infiltrated with rhodamine B and the powder of rhodamine-doped submicrometer silica particles. [10,11] However, in the previous research, the full width at half maximum (FWHM) of the bichromatic lasing peaks was several nanometers; in other words, only the bichromatic incoherent RL was observed. To date, the bichromatic coherent RL emission, the FWHM of which is less than 0.4 nm, has not been demonstrated experimentally.…”
Section: Introductionmentioning
confidence: 89%
“…However, in spite of the large amount of studies related to the PL properties of dyes doped sol-gel samples, only few reports on RL emission were presented. 15,[25][26][27][28] For instance, besides the work reported in Ref.…”
Section: Introductionmentioning
confidence: 93%
“…10-14, there are other possibilities to control the dye photoluminescence (PL) by changing the electronic structure of the molecules, their mutual interaction, the excitation laser intensity, and the influence of the environment. For instance, by exploiting ET processes between monomers and dimers of Rh640, Barbosa-Silva et al 15 demonstrated bichromatic emission that was tuned by adjusting the energy pulse excitation (EPE) incident on a powder consisting of sub-micrometer silica particles, synthesized by the St€ ober modified method, 16 infiltrated with Rh640.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation